Life as market women : Extrinsicly or intrinsicly motivated? - Peter Karubi*, Nwanesi (Universiti Malaysia Sarawak (UNIMAS), 2017)
Wet-markets in Sarawak have remained a momentous part and parcel of the Sarawak people. Such markets exist in both the rural and urban areas of the state, but more importantly, it is popularized by women, either as sellers (traders) or buyers in these markets. The aim of this paper, therefore, is to critically examine the factors that motivate female sellers (market women) in these wet markets to take up this occupation. To empirically explain these factors, the study will explore the notion of extrinsic and intrinsic motivation in relation to women’s participation in the wet market trading activities. Intrinsic motivation is defined as the doing of an activity for its inherent satisfaction rather than for some external influence. In contrast, extrinsic motivation is a behaviour that takes place when one is being influenced to do something by an external force.